Do Natural Resources and Institutional Quality Reduce Energy Intensity? Evidence from Developing and Advanced Economies - Sherif, Menna; Ibrahiem, Dalia M.; El-Aasar, Khadiga M. (Journal of Ecohumanism, 2025)
This study investigates the function of institutions and natural resources in reducing the energy intensity for developing and advanced economies by employing the PCSE estimator and the D-H test. The PCSE estimator indicates that natural resources increase the energy intensity for both economies, and institutions reduce it for developing economies and increase it for advanced economies. The D-H test designates a short-run bidirectional causal relation between natural resources and energy intensity for developing economies and between institutions and energy intensity for advanced economies. The results imply that both economies should enhance their institutional quality and manage natural resource utilization.